The Mediation Role of Marketing Orientation in Relationship between Environmental Friendliness with Customer Green Intention Buying - Mohsen tavakoli khabaz; Hossein norouzi (International Journal of Supply Chain Management, 2018)
As green marketing becomes an essential tool for sustainable business strategy, companies are adopting green marketing practices to achieve better business performance. However, no research has yet operationalized all the organizational facets that are necessary to become a green marketing oriented company. The main purpose of this study is evaluating the impact of environmental friendliness on customer green intention buying with regarding marketing orientation. 12 Hypotheses were generated based on conceptual model. The sample includes 390 customers of Kalleh Company in Iran. The research is based on structural equation modeling (SEM) based on variation (partial least square) and path analysis. The collected data were analyzed by PLS software. The result revealed that there are positive and significant relationship between variables except tactical green marketing orientation and green satisfaction which is not significant. This researchs findings guide managers to develop their business and performance strategies and results and help them to improve the level of customers behaviors. KeyWords marketing orientation, Environmental, customer green intention buying, green trust, green satisfaction